1990
DOI: 10.1016/0014-5793(90)81013-e
|View full text |Cite
|
Sign up to set email alerts
|

The apparent molecular size of native α‐crystallin B in non‐lenticular tissues

Abstract: The apparent molecular size of the native a-crystallin B in cytosol preparations from rat heart, brain and retina was determined by gel permeation chromatography, detecting the protein by immunochemical assay (ELISA), using an a-crystallin specific antiserum. Native a-crystallin from cytosol preparations of rat lens cortex was used as a reference. a-Crystallin B present in all three cytosol preparations from non-lenticular tissues eluted in a single symmetrical peak, with the same elution volume as a-crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…It is possible that aA and aB exist as separate inultimeric forms of similar mass. While this work was in progress, Chiesa et al [42] reported that aB in the extralenticular tissues was an aggregate of about 800 kDa molecular mass, the same as reported earlier for a-crystallin (containing aA and a s ) in the lens by the same laboratory [4]. These investigators did not analyze purified aB to allow a direct assessment of the discrepancy between their and our determinations.…”
Section: Discussionsupporting
confidence: 55%
“…It is possible that aA and aB exist as separate inultimeric forms of similar mass. While this work was in progress, Chiesa et al [42] reported that aB in the extralenticular tissues was an aggregate of about 800 kDa molecular mass, the same as reported earlier for a-crystallin (containing aA and a s ) in the lens by the same laboratory [4]. These investigators did not analyze purified aB to allow a direct assessment of the discrepancy between their and our determinations.…”
Section: Discussionsupporting
confidence: 55%
“…Under normal conditions, small Hsps generally form large oligomers up to ~0.8 MDa in size [19][20][21][22]. There seem to be variations in the apparent stability of the oligomers.…”
Section: Small Hsps Form Large Dynamic Oligomersmentioning
confidence: 99%
“…The oligomeric size of differently phosphorylated Hsp27 was analyzed by size exclusion liquid chromatography using Superose 6. As determined by a number of different methods (12,13,23,38,(42)(43)(44), nonphosphorylated sHsps form complexes of an average molecular mass of 200 -800 kDa indicating a complex of 12 to nearly 40 sHsp monomers. Our analysis shows that nonphosphorylated Hsp27 exhibits an average mass of 530 kDa which correlates with an oligomer of about 24 subunits (Fig.…”
Section: Phosphorylation-regulated Oligomerization Of Hsp27 Inmentioning
confidence: 99%